INVESTIGATION OF DIFFERENT TYPES OF VIDEOS VIEWING FOR OBTAINING RELIABLE MEASUREMENTS PERTAINING TO RESTING ENERGY EXPENDITURE - EBINE, Naoyuki; ICHIKAWA, Seiya (Japanese Journal of Physiological Anthropology, 2021)
This study investigated how various genres of video viewing affected energy expenditure in a sitting position using landscape, horror, and animation videos. Energy expenditures were measured using the Douglas bag method for 12 female university students. The result obtained from each video task was compared with the resting energy expenditure during sedentary seating and showed no difference between energy expenditures while video viewing with resting energy expenditure. In addition, Bland-Altman analysis displayed proportional bias with the landscape video, meanwhile it showed the smallest variation with the animation video. It was indicated that animation videos viewing might be comparable and substitutable to sedentary seating.